Magnetic Nozzle and RPA Simulations vs. Experiments for a Helicon Plasma Thruster Plume - Cichocki, Filippo; Navarro-Cavallé, Jaume; Modesti, Alberto; Ramírez Vázquez, Gonzalo (Frontiers in Physics, 2022)
The experimental characterization of electrodeless plasma thrusters with a magnetic nozzle is fundamental in the process of increasing their maturity to reach the industrialization level. Moreover, it offers the unique opportunity of validating existing numerical models for the expansion of a magnetized plasma plume, and for the synthetic simulation of diagnostics measurements, like those of a retarding potential analyzer, which provides essential information regarding the ion beam energy distribution function. Simulations to experiments comparison ultimately enables a better understanding of the physical processes behind the observed experimental curves. In this work, input experimental data of a Helicon plasma plume is used to simulate both a magnetic nozzle expansion in the divergent field region, and the corresponding measurements of a retarding potential analyzer, through dedicated small-scale simulations of this diagnostics tool. Magnetic nozzle simulation and experimental results agree well in terms of the angular distribution of the ion current at 40 cm distance from the source, and also in the prediction of the energies of the 2 main peaks of the ion energy distribution function: a first one at 45 eV due to source ions, and a second one, at 15-20 eV, due to ions from charge-exchange and ionization collisions in the plume. Finally, the small-scale simulation of the retarding potential analyzer permits to assess the parasitic effects caused by the ion current collected by the different analyzer grids. The inclusion of the retarding and electron suppression grids currents in the overall I-V characteristic is shown to correct almost entirely these effects on the obtained ion velocity distribution.